Efficacy of Sub-Conjunctival Injection of Mitomycin C Versus Bevacizumab in Pterygium Treatment: Pakistani Population - Amber khalid; Sharjeel Sultan; Aveen Fatima; Ayesha Khalid; Maryam Shifa (Pakistan Journal of Medicine and Dentistry)
Background: Pterygium is a progressive fibrovascular tissue that affects the conjunctiva and cornea. The aim of the study was to compare the efficacy of Sub-conjunctival injection of Mitomycin C versus Bevacizumab in pterygium treatment focusing on their impact on recurrence rates to improve postoperative outcomes.